Alguns aspectos da interação fluido-estrutura em estruturas “off-shore” - Pedroso, Lineu José (1982)
The fluid-structure interaction problem is presented in a logical, basic and intuitive systematization, concerning offshore structures. The problem is identified, characterized and classified, as a whole; when particularized to structures in water, it is placed in a fisical and phenomenologic context, in its more qualitative aspects; however, its abordage degenerates in a simplified treatment, through two known classical formulations: (a) Morison's operation, (b) invicit linear difraction theory, involved in all their manifestations and consequences. The magnitude of the interaction effects were quantificated through wave-induced forces, lates compared and estimated its relative importance, in function of certain significant parameters, wich define the nature and domain of these effects. Finally it is studied the dynamic behaviour, of offshore structures, with many of its implications showing some applications and results. To obtain results end the confrontment of this formulations, computer programs were developed and directed to some tipical and significant applicationes, in which complete dynamic hydro-structural analysis were accomplished.